De tule nega à kuna yala. Médiation, territoire et écologie au Panama, 1903-2004 - Mònica Martínez Mauri (Centre de Recherches sur les Mondes Américains, 2008)
This thesis analyses the struggle of the Kuna people of Panamá, for their territory as the sine qua non of their political autonomy and the decisive role indigenous intellectuals have played in this historical process. The main aim of the dissertation is to examine the political and cultural relevance of these intellectuals’ mediation between the Kuna nation and the Panamanian government as well as the international development agencies. I have addressed the classical topics of Kuna ethnography - social change and differentiation – but framed by the ethnographic study of contemporary social and political transformations at the local and global levels. I have paid special attention to the historical emergence of Kuna non governmental organisations (NGO), their activities of transnational mediations and the special relevance ecological issues have acquired among Kuna political claims vis-à-vis Panamanian and international agencies as a way to legitimate their struggle for the acknowledgement of indigenous rights.